Integration of dermoscopy and reflectance confocal microscopy for distinguishing melanomas from nevi of the breast area. (28th November 2017) - Mandel, V.D.; Bombonato, C.; Pampena, R.; Kyrgidis, A.; Borsari, S.; Benati, E.; Mirra, M.; Piana, S.; Pellacani, G.; Longo, C.
Abstract: Background: Nevi of special sites encompass a class of benign lesions characterized by the presence of atypical clinical and histopathological features that can be difficult to distinguish from melanoma. Dermoscopy and reflectance confocal microscopy may improve the clinical assessment of melanocytic lesions to avoid unnecessary excisions. Objectives: The aim of this study was to assess the value of specific dermoscopic and confocal criteria in distinguishing melanomas from nevi of the breast area. Methods: Dermoscopic and confocal images from consecutive patients with at least one clinically and/or dermoscopically equivocal melanocytic skin lesion of the breast area were retrospectively evaluated. In this case–control study, only histopathologically proven melanomas (cases) and nevi (controls) were included. Spearman's coefficients were first calculated to flag significant correlation; then univariate and multivariate logistic regression analyses were performed to assess which factors were independently associated with the histopathological diagnosis. Finally, a mixed dermoscopic/confocal score was created to distinguish nevi from melanomas on the breast area. Results: The study population included 55 skin lesions of the breast area, 34 (61.8%) nevi and 21 (38.2%) melanomas. Among dermoscopic criteria, atypical network and irregular pigmentation resulted independently associated with melanoma diagnosis (OR: 11.1; 95% CI 1.0–119.9; P :0.048 and OR: 6.5; 95% CI 1.1–37.5; P :0.037, respectively). Furthermore, on RCM examination, the presence of pagetoid cells was an independent positive predictor for melanoma (OR: 38.5; 95% CI 3.9–379.6; P :0.002). The mixed score showed high levels of sensitivity and specificity, 95.2% and 82.4%, respectively, which were higher than dermoscopic and confocal evaluations alone. Conclusion: The combined use of dermoscopy and confocal microscopy in the triage of pigmented lesions of the breast area may help in increasing the diagnostic accuracy and avoiding unnecessary excisions.